A Critical Review of Psychological Safety in Psychoeducation for Patients with Anxiety Disorders and Implications for Medical Education in Psychiatry - Chao Tian Tang; Palanivelu Sendhil Kumar; Ho Teck Tan; Siew Fai Liew; Shian Ming Tan (BJPsych Open)
Aims: Psychoeducation for patients with anxiety disorders has been associated with reduced symptoms, improved quality of life, and increased response to treatment. However, there is much heterogeneity in such interventions. Patients with anxiety disorders can have maladaptive cognitive patterns such as catastrophic thinking, attentional biases toward threat, and cognitive avoidance. These patterns can interfere with the processing and assimilation of psychoeducational content, potentially reducing its effectiveness. Our hypothesis is that psychological safety plays a key role in increasing the effectiveness of psychoeducational interventions for patients with anxiety disorders. We aim to critically review the role of psychological safety in such interventions and to explore its impact on medical education in psychiatry.